2022
DOI: 10.1007/s00167-022-07261-3
|View full text |Cite
|
Sign up to set email alerts
|

The traction force of the pulled limb in hip arthroscopic surgery is determined by stiffness coefficient which is significantly related to muscle volume

Abstract: Purpose To verify the relationship between muscle volume, lateral centre-edge angle (LCEA), alpha angle (AA), body mass index (BMI) and Beighton score with stifness coeicient (SC). To analyse the diference of traction force at diferent physical states of hip joint capsule. Methods Thirty-six patients who underwent hip arthroscopy operation were included. The volumes of some related muscles were measured in MRI images by 3D Slicer. We recorded and tested diferences in traction force of ive joint capsule physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Recent research has identified a positive correlation between traction forces and factors such as body weight and the presence of hip osteoarthritis [31]. However, Yin at el suggests lower extremity muscle volume is a greater indicator of higher traction forces than BMI [43]. Thus, these patient factors must be considered when determining risk for patients with prior TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified a positive correlation between traction forces and factors such as body weight and the presence of hip osteoarthritis [31]. However, Yin at el suggests lower extremity muscle volume is a greater indicator of higher traction forces than BMI [43]. Thus, these patient factors must be considered when determining risk for patients with prior TKAs.…”
Section: Discussionmentioning
confidence: 99%